'…But I still can׳t get rid of a sense of artificiality': The Reichenbach–Einstein debate on the geometrization of the electromagnetic field. (May 2016) - Giovanelli, Marco
Abstract: This paper analyzes correspondence between Reichenbach and Einstein from the spring of 1926, concerning what it means to 'geometrize' a physical field. The content of a typewritten note that Reichenbach sent to Einstein on that occasion is reconstructed, showing that it was an early version of Section 49 of the untranslated Appendix to his Philosophie der Raum-Zeit-Lehre, on which Reichenbach was working at the time. This paper claims that the toy-geometrization of the electromagnetic field that Reichenbach presented in his note should not be regarded as merely a virtuoso mathematical exercise, but as an additional argument supporting the core philosophical message of his 1928 monograph. This paper concludes by suggesting that Reichenbach׳s infamous 'relativization of geometry' was only a stepping stone on the way to his main concern—the question of the 'geometrization of gravitation'. Abstract : Highlights: An analysis of a previously neglected Einstein–Reichenbach correspondence is provided. The content of an unpublished note that Reichenbach sent to Einstein is reconstructed. The issue of geometrization in physics is discussed. Reichenbach׳s interpretation of GR is reconsidered in the light of these documents.